Changes in oil content, lipid class and fatty acid composition of the microalga Chaetoceros calcitrans over different phases of batch culture. Issue 10 (27th December 2012) - Miller, Matthew R.; Quek, Siew‐Young; Staehler, Kathrin; Nalder, Tim; Packer, Michael A.
Abstract The diatom Chaetoceros calcitrans is a microalgal species used as food for larva in aquaculture for many species worldwide. Chaetoceros calcitrans is an important source of omega 3 long chain (C ≥ 20) polyunsaturated fatty acids (n‐3 LC PUFA), chiefly eicosapentaenoic acid (EPA, 20:5n‐3). This article reports lipid content, lipid class composition and fatty acid profiles of each lipid class during the growth cycle of batch cultures of C. calcitrans. Total lipid content and the concentration of neutral lipid were highest in the late stationary growth phase (day 12). However, the amount of EPA was highest during the logarithmic growth phase (1.24 pg/cell on day 4). EPA was initially concentrated in the glycolipid fraction, but this fraction decreased during logarithmic growth, coinciding with the increase in neutral lipid. Docosahexaenoic acid (22:6n‐3, DHA) (0.91 pg/cell) was reported as a major fatty acid (>10 mg/100 g) in all lipid classes on day 1. DHA was depleted quickly from the neutral lipid and glycolipid classes, but at a slower rate from the polar lipid fraction. This work confirms that C. calcitrans is a good source of lipid, in particular EPA, for larval and adult filter feeders in aquaculture.